2006
DOI: 10.1021/la0533009
|View full text |Cite
|
Sign up to set email alerts
|

Semifluorinated Chains at the Air/Water Interface:  Studies of the Interaction of a Semifluorinated Alkane with Fluorinated Alcohols in Mixed Langmuir Monolayers

Abstract: Mixtures of a semifluorinated alkane 1,1,1,2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10-henicosafluorotriacontane (abbr. F10H20) and different alcohols were investigated at the air/water interface using surface pressure-area isotherms complemented with BAM images. In our studies, octadecanol and its fluorinated derivatives differing in the degree of fluorination were researched. To verify the influence of an iso branching of the fluorinated segment in an alcohol molecule, the properties of perfluorooctyldecanol and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…Seoane et al [34] reported mixed films of cholesterol with saturated or unsaturated fatty acids, but these are not discussed here due to the peculiar characteristics of cholesterol. Several authors [23,[25][26][27]30,32] have also observed phase separation in fatty acid mixed monolayers of fluorinated and hydrogenated amphiphiles.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Seoane et al [34] reported mixed films of cholesterol with saturated or unsaturated fatty acids, but these are not discussed here due to the peculiar characteristics of cholesterol. Several authors [23,[25][26][27]30,32] have also observed phase separation in fatty acid mixed monolayers of fluorinated and hydrogenated amphiphiles.…”
Section: Discussionmentioning
confidence: 92%
“…One of the main aspects of these mixtures is the miscibility and phase separation. Recent articles on mixed fatty acids systems are those of [23][24][25][26][27][28][29][30][31][32]. Furthermore, since fatty acids or phospholipids usually present unsaturations in the hydrocarbon chains, the study of mixtures of saturated and unsaturated compounds is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The net interaction between two components in a mixed monolayer, at a constant surface pressure and absolute temperature T, can be evaluated from the calculation of excess Gibbs energy ( G E mix ) and the interaction parameter (˛) [12,13,16,19], which are given by:…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Since the values of the first virial coefficient (b 0 ) were lower than 1 for all studied systems, two-dimensional molecular aggregates existed at low pressures. Thus their aggregation number (1/b 0 ) could be estimated [19], see Table 4. This could be indirectly related to the existence of laterally structured microdomains.…”
Section: Equation Of State Analysismentioning
confidence: 99%
“…The ΔV-A isotherms of FnCOOH monolayers indicate changes in molecular orientation upon compression; similarly, the ΔV value of hydrogenated lipid monolayers indicates positive variation in molecular orientation upon compression. However, the isotherms of the F-chains have an sign opposite to those of hydrogenated lipid monolayers or exhibit negative variation due to the electronegativity as the molecular areas decrease, which has been thoroughly discussed 16,32,34,35,37,40,69 . Recently, it has been reported that the monolayers of ethers having a long-chain hydrocarbon and a fluorinated headgroup exhibit large negative ΔV values 70 72 .…”
Section: Thermal Properties Of Fncoohmentioning
confidence: 99%